No fact of the middle. (12th September 2021) - Khoo, Justin
Abstract: A middle fact is a true proposition about what would have happened had A been true (where A is in fact false), whose truth isn't entailed by any non‐counterfactual facts. I argue that there are no middle facts; if there were, we wouldn't know them, and our ignorance of them would result in ignorance about whether regret is fitting in cases where we clearly know it is. But there's a problem. Consider an unflipped fair coin which is such that no non‐counterfactual fact determines that it would have landed heads had it been flipped (or tails had it been flipped). If there are no middle facts, it's not true that it would have landed heads had it been flipped nor that it would have landed tails had it been flipped. Yet each counterfactual is still possibly true for all we know. I argue that we can resolve this tension in the anti‐middle fact position, further strengthening the case against middle facts.